Image-based tracking system for rotating object vibration measurement using laser scanning vibrometer - Kim, Dongkyu; Khalil, Hossam; Nam, Joonsik; Park, Kyihwan (International journal of precision engineering and manufacturing, 2015)
An image-based tracking system using a laser scanning vibrometer is developed for vibration measurement of a rotating object in order to take advantage of rotation tracking without attaching an external sensor such as an encoder to the object. An image processing algorithm is used to detect a landmark and laser beam and track all vibration measuring points on a rotating object. To verify the performance of the proposed tracking system, processing time analysis of the image processing algorithm is carried out. The accuracy of the tracking system is also experimentally tested. Finally, the experimental results of modal analysis of the object without and with rotation are compared and the vibration measurement of the object is validated.